Optimization of a home hospitalization program for hematopoietic stem cell transplantation with ehealth integration and clinical pharmacist involvement - Moreno-Martinez, Maria-Estela; Riba, Mireia; García-Cadenas, Irene; Esquirol, Albert; Yusta, Marta; Redondo, Sara; De Dios, Anna; Portos, Jose Manuel; Aso, Olga; Marcos-Fendian, Angel; Font, Núria; Briones, Javier; et al. (Frontiers in Immunology, 2024)
Home hospitalization represents an alternative to traditional hospitalization, providing comparable clinical safety for hematological patients. At-home therapies can range from the delivery of intravenous antibiotics to more complex scenarios, such as the care during the early period after hematopoietic stem cell transplantation and chimeric antigen receptor T-cell therapy. Early discharge from conventional hospitalization is feasible and helps reduce hospital resources and waiting lists.The coordinated efforts of multidisciplinary teams, including hematologists, nurses, and pharmacists, ensure patient safety and continuity of care. The traditional model of home hospitalization relies on home visits and telephone consultations with physicians and nurses. However, the use of eHealth technologies, such as MY-Medula, can enhance communication and monitoring, and thereby improve patient outcomes with no additional costs.The active involvement of a clinical pharmacist in home hospitalization programs is essential, not only for the proper logistical management of the medication but also to ensure its appropriateness, optimize treatment, address queries from the team and patients, and promote adherence.In conclusion, the implementation of hematopoietic stem cell transplantation and chimeric antigen receptor T-cell therapy home hospitalization programs that use both an eHealth tool and a multidisciplinary care model can optimize patient care and improve quality of life without increasing healthcare costs.